A PLC controlled model of a drinking water packager assembly line - Sheik Ihsanuddin, Sheik Khairul Anwar (2006)
A model of a packaging assembly line is constructed and is to be controlled by a Programmable Logic Controller (PLC). The assembly line mainly consists of a conveyor system with four stations to execute specific tasks. These stations are equipped with sensors, actuators, and indicators to help students visualize the role of PLC in the production industry. It is hoped that students will understand better the operations and applications of ladder programming and the PLC.